(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
In the current era of industrial and enterprise evolution, time and resource are the fundamental need of any industry. Utilizing the time and resource has always been the primary goal of especially a construction project in order to reduce the expenses, meet the project deadlines and accomplish the work successfully. Lean approach in the construction industry has been introduced to facilitate and manage such procedure to achieve the above-mentioned goals of a company. Construction industry has also adapted this approach under the title of lean construction to give boast in the process of construction projects by applying the lean construction techniques. In this research, we have tried to discover the lean construction barriers in the construction industry and limitations of implementing lean construction in construction industry worldwide. The barriers have been gathered through an extant literature survey and then concluded by defining them among different categories of professionals. It is concluded that overcoming the barriers would lead to less wastage in the construction industry and lead to more efficiency and productivity.